1992
DOI: 10.1017/s0142716400005555
|View full text |Cite
|
Sign up to set email alerts
|

The role of feedback in adult second language acquisition: Error correction and morphological generalizations

Abstract: This study looked at the effects of feedback (explicit correction) on the learning of morphological generalizations in an experimental setting. Subjects were 79 adult native speakers of English with intermediate (39) and advanced (40) levels of proficiency in French. All subjects were individually trained on two rules of French suffixation. Experimental subjects received correction if they gave erroneous responses to stimuli in a "feedback" session. Afterward, all subjects "guessed" responses to novel stimuli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 36 publications
1
56
0
2
Order By: Relevance
“…provided reviews of the research on recasts+ In general, the recast studies demonstrated that implicit feedback of this kind can have a beneficial effect on acquisition, especially when the recasts are more explicit in nature~as in Doughty & Varela, 1998!+ Other studies demonstrated that explicit feedback is of value+ Carroll, Roberge, and Swain~1992!, for example, found that a group that received explicit corrective feedback directed at two complex French noun suffixes~-age and -ment! outperformed a group that received no feedback, although no generalization of learning to nouns not presented during the treatment occurred+ Thus, the recast and explicit feedback studies demonstrated that both types of feedback can be effective+ Table 1 summarizes 11 studies that have compared implicit and explicit corrective feedback+ It is not easy to come to clear conclusions about what these studies reveal due to a number of factors+ First, whereas some of the studies are experimental in nature~e+g+, Carroll, 2001;Carroll & Swain, 1993;Lyster, 2004;Rosa & Leow, 2004!, others are not~e+g+, DeKeyser, 1993Havranek & Cesnik, 2003!, as this second group of researchers investigated corrective feedback through post hoc analyses of normal classroom lessons+ Second, the studies vary in terms of whether they involved laboratory, classroom, or computer-based interaction+ Third, the nature of the treatment activities performed by the learners in these studies differed considerably+ In some cases, the activities involved fairly mechanical exercises~e+g+, Nagata, 1993!, in others they involved communicative tasks~e+g+, Leeman, 2003Muranoi, 2000;Rosa & Leow!, and in others they involved a mixture of the two~DeKeyser!+ Fourth, the treatment also differed in terms of whether it …”
Section: Previous Research On Corrective Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…provided reviews of the research on recasts+ In general, the recast studies demonstrated that implicit feedback of this kind can have a beneficial effect on acquisition, especially when the recasts are more explicit in nature~as in Doughty & Varela, 1998!+ Other studies demonstrated that explicit feedback is of value+ Carroll, Roberge, and Swain~1992!, for example, found that a group that received explicit corrective feedback directed at two complex French noun suffixes~-age and -ment! outperformed a group that received no feedback, although no generalization of learning to nouns not presented during the treatment occurred+ Thus, the recast and explicit feedback studies demonstrated that both types of feedback can be effective+ Table 1 summarizes 11 studies that have compared implicit and explicit corrective feedback+ It is not easy to come to clear conclusions about what these studies reveal due to a number of factors+ First, whereas some of the studies are experimental in nature~e+g+, Carroll, 2001;Carroll & Swain, 1993;Lyster, 2004;Rosa & Leow, 2004!, others are not~e+g+, DeKeyser, 1993Havranek & Cesnik, 2003!, as this second group of researchers investigated corrective feedback through post hoc analyses of normal classroom lessons+ Second, the studies vary in terms of whether they involved laboratory, classroom, or computer-based interaction+ Third, the nature of the treatment activities performed by the learners in these studies differed considerably+ In some cases, the activities involved fairly mechanical exercises~e+g+, Nagata, 1993!, in others they involved communicative tasks~e+g+, Leeman, 2003Muranoi, 2000;Rosa & Leow!, and in others they involved a mixture of the two~DeKeyser!+ Fourth, the treatment also differed in terms of whether it …”
Section: Previous Research On Corrective Feedbackmentioning
confidence: 99%
“…or input processing~Rosa & Leow; Sanz, 2003!+ Fifth, the studies vary considerably in how they operationalized implicit and explicit feedback+ Given the importance of this variable, it is discussed in greater detail later in this section+ Sixth, variation is evident in how learning was measured: Some studies utilized metalinguistic judgments~e+g+, Muranoi!, selected response, or constrained constructed response formats~e+g+, Havranek & Cesnik; Rosa & Leow!, all of which might be considered to favor the application of explicit knowledge, whereas others opted for a free constructed response format~e+g+, Leeman!, which is more likely to tap implicit knowledge+ Finally, the studies differ in another important respect: Some included an explicit explanation of the grammatical target prior to the practice activity~e+g+, Lyster; Muranoi!, whereas others did not e+g+, Leeman; Sanz!+ These differences in design reflect the different purposes of the studies, not all of which were expressly intended to compare implicit and explicit corrective feedback+ Implicit feedback in these studies has typically taken the form of recasts Carroll, 2001;Carroll & Swain, 1993;Kim & Mathes, 2001;Leeman, 2003;Lyster, 2004!+ However, Muranoi~2000! employed both recasts and requests for repetition+ Sanz~2003!…”
mentioning
confidence: 99%
“…Researchers look into such matters as different types of correction, general issues related to correction (Chandler, 2003;Chaudron, 1986;James, 1998;Truscott & Hsu, 2008;Zybert, 1999), substantiation of positive approach to language mistakes, (Bartram & Walton, 1991), implicit and explicit corrective feedback (Ellis, Loewen & Erlam, 2006), oral and written corrective feedback (Bitchener & Knoch, 2010;Ellis, 2010), prompts and recasts (Ammar, 2008), errors as indicators of the development of interlanguage (Arabski, 1979), feedback in adult second language acquisition (Carrol, Swain & Roberge, 1992), individual differences in second language learning and difficulties caused by them (Ellis, 2004), modelling learning difficulties (Ellis, 2006), analysing learner language (Ellis & Barkhuizen, 2005), the short-and long-term effects of written error correction (Ferris, 2006), effects of proficiency differences and patterns of pair interaction on second language learning (Watanabe & Swain, 2007).…”
Section: Problem Statementmentioning
confidence: 99%
“…The issues discussed include when, which, and how errors should be corrected, as well as whether learners' errors should be corrected at all. Among the examined issues, the question of whether learners should be corrected has been investigated in studies such as Carroll, Roberge, and Swain (1992) and Carroll and Swain (1993), both of which dealt with the provision of corrective feedback on certain linguistic forms, in a controlled experimental setting. The study of Carroll et al (1992) examined adult French learners who were trained in use of French suffixation rules and given feedback on their misuse.…”
Section: Theoretical Background On Corrective Feedbackmentioning
confidence: 99%
“…Among the examined issues, the question of whether learners should be corrected has been investigated in studies such as Carroll, Roberge, and Swain (1992) and Carroll and Swain (1993), both of which dealt with the provision of corrective feedback on certain linguistic forms, in a controlled experimental setting. The study of Carroll et al (1992) examined adult French learners who were trained in use of French suffixation rules and given feedback on their misuse. Carroll and Swain (1993), on the other hand, investigated adult English learners who were given different kinds of feedback while learning the English dative alternation rule.…”
Section: Theoretical Background On Corrective Feedbackmentioning
confidence: 99%